Automation of Daily Access Data Recap of Employee Data Tables Using Apps Script to Detect Illegal Activities: - Jong, Jek Siang; Rivanka, Rio Rian; Wibowo, Argo (Universitas Mohammad Husni Thamrin, 2025)
Currently, data security is very crucial in a company. Data hacking is increasingly common. Tokopedia experienced a data hack estimated at 91 million user accounts and 7 million merchant accounts. This data is then sold via the dark web, which seriously endangers user privacy and safety. Protection of personal data against hackers from outside is increasingly needed. Management of data recaps and monitoring employee data access in the largest retail company in Indonesia is carried out by the Human Resources division. Due to the large number of employees, daily access to employee data such as attendance is prone to misuse because detection of illegal activities on data is still done manually. In this research, a system based on Google Spreadsheet and Apps Script was created. which is able to detect illegal activities against employee databases. The system is able to accurately categorize logs based on account and IP address, distinguishing between normal and suspicious logs. The system is able to convert a spreadsheet containing data access recaps into an Excel file and send it to the specified email. System testing was carried out on Human Resources division employees through 6 tests on all system features. The results show that all system outputs are exactly as expected. The system helps Human Resources division employees observe data changes without having to access the database, making it easier to detect illegal data access.